The Use of Bone Morphogenetic Protein in Spinal Transforaminal Lumbar Interbody Fusion: Our Experience - Colom-Beauchamp, Eduardo; Beaton-Comulada, David; Rodriguez, Julio A.; Pérez-López, José C.; Montañez-Huertas, José; Escobar-Medina, Enrique; Massanet-Vollrath, José (Puerto Rico Health Sciences Journal, 2017)
Objective: Since its introduction and FDA approval, rhBMP-2 has been adopted by spine surgeons as a substitute for ICBG in numerous spinal fusion techniques. As broad clinical use increased, reports on potential complications associated with rhBMP-2 also increased. We provide our experience with TLIF using rhBMP-2 or ICBG in an entirely Hispanic population. Methods: This was a 2-year retrospective study of 67 patients, with 26 in the rhBMP-2 group and 41 in the ICBG group, who underwent TLIF. Pertinent information was obtained through review of the medical records documenting complications, intraoperative times, and EBL, among other things. Results: There were 28 post-operative complications with 15 (53.6%) in the ICBG group and 13 (46.4%) in the rhBMP-2 group. The average EBL was 572.3 mL (SD: 411.8) in the ICBG group and 397.9 mL (SD: 312.2) in the rhBMP-2 group. The average intraoperative time was 243.1 minutes (SD: 79.5) in the ICBG group and 226.5 minutes (SD: 64.7) in the rhBMP-2 group. Fifty-two patients underwent open TLIF and 15 patients underwent MI TLIF. The average EBL was 571.2 mL (SD: 375.3) in the open TLIF group and 228.3 mL (SD: 299.3) in the MI-TLIF group. The average intraoperative time was 241.0 minutes (SD: 76.0) for patients in the open TLIF group and 218.8 minutes (SD: 65.0) for those in the MI-TLIF group. There were no new cancer events at any of the 2-year follow-up visits. Conclusion: Our results suggest that the safety profile of rhBMP-2 may be inferior to that of ICBG, rejecting the possibility of ICBG being replaced by rhBMP-2 as the gold standard for spinal fusion.